PROBLEMATIKA PENETAPAN TERSANGKA YANG MENGALAMI GANGGUAN JIWA DALAM TAHAP PENYIDIKAN - Fajari, M.; Tornado, Anang S. (Universitas Muara Bungo, 2025)
This research aims to determine the legal mechanism for determining someone as a suspect who is suspected of having a mental disorder at the investigation stage, as well as to find out solutions that can be applied to overcome problems in determining a suspect with a mental disorder at the investigation stage. This research is normative legal research that is prescriptive in nature with a conceptual approach and a statutory approach. The types of materials used are primary and secondary legal materials. Based on this research, the results obtained are that investigators are still obliged to examine the case and complete the examination agenda file until it is complete, to then hand it over to the prosecutor's office and the court. The authority to decide a person's criminal responsibility rests entirely with the judge, although police investigators can seek advice from a doctor or psychiatrist. If the judge decides that the perpetrator is truly irresponsible, then the perpetrator is released from all legal charges. However, for the safety of the perpetrator and the community, the judge can order the perpetrator to be placed in a mental hospital for a maximum probation period of one year, in accordance with Article 44 paragraph (2) of the Criminal Code. Regulatory and Policy Reform is very important because, KUHAP and Mental Health Law: Consider revising the KUHAP and Mental Health Law to further clarify procedures for handling suspects with mental disorders, including their rights, observation time limits, and mechanisms for placement in mental health facilities as a substitute for detention.Key words: Mental Disorders, Investigation, Suspects